Hubungan Indeks Masa Tubuh (IMT) Dengan Body Image Pada Siswa SMA PGRI Jakarta Timur - Rosidawati Rosidawati; Pudjiati Pudjiati; Prayetni Prayetni (Jurnal Keperawatan, 2019)
Dissatisfaction with body shape, often found in adolescents This makes teenagers apply various ways to get the ideal body by carrying out an extreme diet, adolescents often get stuck with unhealthy eating patterns. Teens want drastic weight loss, so that they apply inappropriate behavior in reaching the ideal body. This study aims to determine the relationship between BMI and Body Image. Non-experimental research design (cross sectional) was applied where the population is all PGR Senior High School students in Cipayung sub-district, East Jakarta. The number of samples analyzed was 202 respondents. Analysis of the data that is used was univariate, Chi-square and multivariate tests (Simple Logistic Regression). The results of the study found a significant relationship between BMI and Body Image, no significant relationship between age and body image, there is asignificant relationship between gender and body image. Recomended that the PGRI High School education will further enhance cooperation with the Puskesmas related to the implementation of health education on balanced nutrition so that students are more confident about body image and health.